Manajemen Sarana Prasarana di Day Care Baby’s Home Salatiga - Desi Kusumawati (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2017)
Day Care is one form of early childhood education in non formal education program that organize nurturing and social welfare of children from birth up to the age of 6 years. This study aimed to identify the suitability of existing infrastructure in Baby's Home day care with the ACT of Minister of Education and Culture No. 137 of 2014 Article 32 Paragraph 3; and to provide an overview why the planning, maintenance and inventory in Baby's Home day care were not optimal. This study was qualitative research. The subject was Baby's Home day care Salatiga. Technique of collecting data using interviews, observation and documents. Data were analyzed using Miles and Huberman Model. Data validation using triangulation technique of data. Facilities and infrastructure in Baby's Home day care which conform with ACT of Minister of Education and Culture No. 137 of 2014 Article 32 Paragraph 3 of were the area of land, space of activities inside and outside, hand washing facilities, showers and latrines, and access to health facilities. While things were not conform included the bedroom, dining room, and covered trash. The cause of the planning, maintenance and inventory of facilities and infrastructure have not optimally done because the plan was not carried out continuously, the lack of personnel to assist in the maintenance, and did not have the administrative staff specifically for inventory. Advice can be given to Baby's Home day care is to conduct procurement planning infrastructure on sleeping room, dining room and trash. In addition, the maintenance to existing infrastructure must be made as well as the inventory of infrastructure in order to facilitate the planning purchasing.